Analysis of the Regional Warrior Figure Christoffel Binti as a Teaching Material for History of Heroism Material for Class XI MIPA 8 Students at SMA Negeri 2 Palangka Raya - Injili, Putri Oktamala; Susanto, Yudi (Universitas Syiah Kuala, 2025)
This study aims to analyse the local hero Christoffel Binti as historical teaching material on heroism, which was tested on the students of Class XI MIPA 8 at Palangka Raya Senior High School 2. In Indonesia, particularly in Central Kalimantan, the integration of local figures into educational curricula remains insufficient, despite these figures being highly relevant examples with significant historical value for enriching students' understanding of local history and the values of heroism and struggle. This research employs a mixed-method approach, where qualitative data were obtained through interviews with history teachers and observations of the learning process, while quantitative data were collected through questionnaires completed by the students of Class XI MIPA 8 at Palangka Raya Senior High School 2. Quantitatively, the results showed that the overall average percentage score of students' pretests was 52.5%, and after the treatment (introduction of Christoffel Binti teaching material), the overall average percentage score of the post-test increased to 92%, indicating a 39.5% improvement from pretest to post-test. This data suggests that the use of the local figure Christoffel Binti in history teaching materials received very positive responses from students, who felt they gained a better understanding of heroism through this local figure. The teachers also supported the integration of local figures into the learning activities, although there are challenges in developing appropriate teaching materials. The findings of this study highlight the importance of introducing local figures in teaching materials to enrich students' knowledge of history and instil the values of heroism.